The British and Irish Ruling Class 1660-1945 Vol. 2 - Wasson, Ellis A. (Berlin/Boston De Gruyter, 2021)
The book provides a comprehensive reference source for the governing class of Great Britain and Ireland from Oliver Cromwell to Winston Churchill, and offers a deep pool of data to support analysis of social, political, economic, and cultural history in the British Isles over the course of more than four centuries.
English
Keywords: British & Irish history; Modern history to 20th century: c 1700 to c 1900; 20th century history: c 1900 to c 2000; Economic history; British Parliament; Irish Parliament; Scottish Parliament; Wales; elite; landed gentry; House of Commons; House of Lords; social mobility; aristocracy; class